Pelatihan Canva untuk Guru SD Sekecamatan Majenang Kabupaten Cilacap - Zainal Arifin; Tri Angkarini; Nini Adelina Tanamal; Edward Alfin; Ricky Eka Sanjaya (Indo Publishing, 2025)
This training program was designed to improve the competence of elementary school teachers in creating visual-based instructional media using the Canva application. Held for teachers in Majenang District, Cilacap Regency, the training combined theoretical lectures, live demonstrations, and hands-on practice to ensure comprehensive understanding and skill acquisition. At the outset, a pre-test was conducted to assess the participants’ initial knowledge and digital design skills. The results showed an average score of 58.3, indicating limited experience with design tools and low literacy in visual media creation. Following the training, a significant improvement was observed. A total of 90% of the participants successfully produced at least two educational media products, such as posters, infographics, and activity cards. The post-test results revealed an average score of 86.7, demonstrating a substantial increase in understanding and practical ability. Additionally, the satisfaction survey showed that 92% of participants were very satisfied with the content, delivery method, and technical assistance provided during the sessions. This outcome highlights the effectiveness of the training in empowering teachers to utilize Canva for innovative and engaging learning materials. The participants are now better equipped to apply these skills in their classrooms, contributing to a more visually appealing and interactive learning environment.